Principle component analysis of organoleptic acceptability on Cocos™ emulsion product - Koh, Soo Peng; Khor, Yih Phing; Tan, Chin Ping; Hamid, N. S. A.; Long, Kamariah; Long, Shariah Loh (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
Cocos™ Emulsion is new food emulsion product that made of virgin coconut oil (VCO). A sensory analysis was conducted among targeted consumers, which were 150 schoolchildren (age 4 - 12) and 100 adult panelists (age 21 - 60). The principle component analysis (PCA) was applied to assess the organoleptic acceptability of public and schoolchildren on this novel product. In summary, both adult and schoolchildren panelists showed a significant preference (P < 0.05) toward Cocos™ Emulsion than VCO for both sensory attributes of taste and odour, as it was palatable. The scores plot of sensory attributes among all panelists were found highly scattered around, indicating no age-dependent preference on the sensory rating of each attributes.